Evaluating the effect of dental explosion boxes on oral health awareness in preschoolers - Dewi Sodja Laela; Indah Fauziah; Ulfah Utami; Megananda Hiranya Putri; Yonan Heriyanto; Neneng Nurjanah; Irwan Supriyanto; Deru Marah Laut; Nurul Fatikhah; Devy Octaviana (PAGEPress Publications, 2023)
Many children experienced anxiety during their initial dental visits, often fearing medical equipment and the procedures they would undergo. The Dental Explosion Box served as an alternative approach to enhance oral health awareness and functioned as an educational tool integrated with a game. This study aimed to assess the effectiveness of the Dental Explosion Box in introducing oral health concepts to early childhood. This research employed a pre-experimental design featuring a one-group pre-test and post-test approach. Sampling relied on the purposive sampling technique, with the sample size determined using the Isaac and Michael formula, resulting in a cohort of 25 preschool students. Variables examined in this study encompassed the Dental Explosion Box and Oral health Awareness. Oral health awareness in preschool children was measured using a checklist of questions. The Dental Explosion Box had undergone rigorous testing and had been endorsed by media and material experts. The study's hypotheses were tested using the Wilcoxon Sign Rank Test. The average pre-intervention oral health introduction score was 6.68, while the post-intervention score increased to 11.00. Analysis through the Wilcoxon Sign Rank Test revealed a significant difference (p-value of 0.000, <0.05) between the level of oral health awareness in early childhood before and after receiving intervention with the Dental Explosion Box. The findings from this study highlighted the effectiveness of the Dental Explosion Box in introducing oral health concepts to early childhood. It enhanced children's familiarity with oral health and motivated them to regularly visit the dentist.